Improving Teacher Organizational Citizenship Behavior (OCB) Through Strengthening Transformational Leadership and Self-Efficacy - Andi Hermawan; Daisy Radnawati (Krisnadwipayana International Journal of Management Studies, 2024)
The success and sustainability of an organization are largely determined by the willingness of employees to behave well not only when carrying out their main tasks, but also extra behavior in wanting to be good teachers. However, there are indications that teachers at the PGRI Vocational School in Bogor Regency only carry out basic tasks and do not demonstrate behavior that supports organizational effectiveness outside of this. This research aims to determine the relationship between Transformational Leadership and Self-Efficacy in Organizational Citizenship Behavior both partially and jointly. The population in this study were teachers at the PGRI Vocational School, Bogor Regency with a sample of 243 respondents. Data collection was carried out by distributing questionnaires and data processing was carried out by using simple regression analysis and multiple regression analysis. The research results show that (1) Transformational Leadership has a positive and significant relationship with teachers' Organizational Citizenship Behavior. (2) Self-efficacy has a positive relationship with teacher Organizational Citizenship Behavior. (3) Transformational Leadership and Self-Efficacy together have a positive and significant relationship with teachers' Organizational Citizenship Behavior.